EFFECTIVENESS OF CLOSE KINETIC CHAIN TRAINING METHOD WITH ISOMETRIC QUADRICEPS ON INCREASING QUADRICEPS MUSCLE STRENGTH IN OSTEOARTHRITIS PATIENTS - wishnu, Wishnu Subroto SST.FT, S.Ft.,M.Or; Danang, Bejo; Kasron (Gamma Publishing, 2025)
Osteoarthritis (OA) is a degenerative joint disease with unclear etiology and pathogenesis, characterized by gradual loss of joint cartilage. The primary abnormality in OA is cartilage damage, which can be followed by subchondral bone thickening, osteophyte growth, ligament damage, and mild inflammation of the synovium, resulting in the formation of an effusion in the affected joint. Osteoarthritis generally affects older individuals, particularly weight-bearing joints, such as the knee, hip (coxa), lumbar, and cervical joints. The knee is the most frequently affected joint by OA. One symptom of knee osteoarthritis is pain. This pain can cause a person to fear activity or movement, thus reducing their quality of life. Recommended non-pharmacological therapies include exercise. Other types of exercise that can be done include home exercises, Range of Motion (ROM), strengthening exercises including quadriceps and hamstring exercises, and aerobics such as walking, cycling, and swimming. The goals of this exercise include improving joint function, increasing joint trength, protecting joints from damage by reducing stress, preventing disability, and improving physical fitness. These exercises are tailored to the patient's condition and abilities.The purpose of this study was to determine the effectiveness of Closed Kinetic Chain exercises with Isometric Quadriceps on increasing muscle strength in patients with knee osteoarthritis. Methods: This study used a quasi-experimental method with a randomized pretest-posttest. Twenty patients participated using ordinal regression statistical tests. Inclusion criteria were those over 40 years of age with a diagnosis of osteoarthritis and willing to participate. Results: Closed Kinetic Chain exercises were statistically effectivein increasing muscle strength with a probability value (p=0.005). Conclusion: Based on the analysis and statistical test calculations, the following conclusions can be drawn: 1) Closed Kinetic Chain exercises are effective in increasingquadriceps muscle strength in patients with osteoarthritis. 2) Isometric quadriceps exercises are effective in increasing muscle strength in patients with osteoarthritis. 3) There is a difference in the effectiveness of closed kinetic chain and isometric quadriceps exercises in increasing muscle strength in people with knee osteoarthritis.